Simplified polyp-canal system of stony coral Seriatopora hystrix protects its branching areas in the flow field - Li, Yixin; Lu, Zuhong; Zhao, Yunpeng; He, Chunpeng (Frontiers in Marine Science, 2025)
The polyp-canal system is vital for the growth, budding, and mineralization of scleractinian corals. Seriatopora hystrix displays a unique structural trait, with its calices and canals making up only about 15% of the colony volume, lower than the 40-50% observed in other widely distributed genera such as Acropora, Montipora, Pocillopora, or Stylophora. We used micro-computed tomography to visualize the polyp-canal system of S. hystrix, quantify its growth parameters, and simulate the dynamic processes of polyp budding and movement. It reveals that the polyps in S. hystrix follow the budding pattern of unilateral extension along the growth axis and radiates within the horizontal plane, which simplifies its polyp-canal system. Through the finite element analyses under average and maximum wave velocities of South China Sea, we measured the stress distribution in coral models with varying canal volume proportions. We found that the lower volume proportion of polyp-canal system in S. hystrix reduces the VonMises stress at the branching areas by approximately 40-50%, ensuring the continual construction of branchlets in high speed flow field. This study enhances our understanding of Seriatopora coral growth patterns and their adaptation to marine environments, contributing to the species selection in coral reef restoration.